Vascular Dysfunction in Diabetes and Obesity: Focus on TRP Channels - Moraes, Raiana dos Anjos; Webb, R. Clinton; Silva, Darízy Flávia (Frontiers in Physiology, 2021)
Transient receptor potential (TRP) superfamily consists of a diverse group of non-selective cation channels that has a wide tissue distribution and is involved in many physiological processes including sensory perception, secretion of hormones, vasoconstriction/vasorelaxation, and cell cycle modulation. In the blood vessels, TRP channels are present in endothelial cells, vascular smooth muscle cells, perivascular adipose tissue (PVAT) and perivascular sensory nerves, and these channels have been implicated in the regulation of vascular tone, vascular cell proliferation, vascular wall permeability and angiogenesis. Additionally, dysfunction of TRP channels is associated with cardiometabolic diseases, such as diabetes and obesity. Unfortunately, the prevalence of diabetes and obesity is rising worldwide, becoming an important public health problem. These conditions have been associated, highlighting that obesity is a risk factor for type 2 diabetes. As well, both cardiometabolic diseases have been linked to a common disorder, vascular dysfunction. In this review, we briefly consider general aspects of TRP channels, and we focus the attention on TRPC (canonical or classical), TRPV (vanilloid), TRPM (melastatin), and TRPML (mucolipin), which were shown to be involved in vascular alterations of diabetes and obesity or are potentially linked to vascular dysfunction. Therefore, elucidation of the functional and molecular mechanisms underlying the role of TRP channels in vascular dysfunction in diabetes and obesity are important for the prevention of vascular complications and end-organ damage, providing a further therapeutic target in the treatment of these metabolic diseases.